Tribal Sabbaths: Rest Days in the Bible and in African Traditional Religions - Bridges, Carl B; Cook, L. Stephen Jr. (Stone-Campbell Journal, 2016)
The people of Israel took a weekly day of rest in honor of their God, and some people in traditional societies in Africa do the same today. This paper explores the motives for Sabbath-keeping reflected in the Hebrew Bible, the Apocrypha, and the New Testament alongside the motives of traditional African people today for keeping their tribal sabbaths. We argue that motives for Sabbath-keeping in the Israelite tradition included ritual, national, and humanitarian concerns, that both Jesus and Paul relativized the practice and minimized ritual motives, and that the known traditional African restdays emphasize ritual requirements at the expense of humanitarian concerns. This study falls into five unequal parts: 1) a survey of the Sabbath in the Hebrew Scriptures, 2) a reference to some relevant passages in the Apocrypha, 3) a discussion of the Sabbath in the New Testament, 4) ethnographic information on Sabbathlike days in tribal Africa, and 5) a comparison and contrast of the biblical Sabbath and the tribal sabbaths.
free
Keywords: Bible – Criticism; interpretation – History; Christianity and indigenous religions; Folk religion; African; Sabbath – Biblical teaching